Oceanic and ecological response to native Typhoons Cempaka and Lupit (2021) along the northern South China Sea continental shelf: comparison and evaluation of global and regional Operational Oceanography Forecasting Systems - Guo, Shaojing; Zhu, Xueming; Ji, Xuanliang; Wang, Hui; Zhang, Shouwen; Jiang, Hua; Wang, Dan (Frontiers in Marine Science, 2023)
The in situ and satellite observations were employed to compare and evaluate the Global Operational Oceanography Forecasting System from Mercator Océan (MO) and the regional South China Sea Operational Oceanography Forecasting System (SCSOFSv2), with focuses on oceanic and ecological responses to two consecutive native typhoons Cempaka and Lupit in July-August 2021. Results show that SCSOFSv2 performs better in simulating structure of Chla, while MO exhibits a well simulation of the temperature profile in the Pearl River Estuary. On the contrary, variations of SCSOFSv2 SST (MO Chla) are in good correspondence with observations along the northern SCS shelf. Simulated maximum SST cooling is larger and 2 3 days earlier than observations. Maximum Chla is stronger and leading about 2 days than that of climatological average after passage of typhoon. Typhoon-induced vertical variations of Chla and NO3 indicate different processes of Chla bloom from the coastal waters to continental shelf. Discharge brings extra nutrients to stimulate Chla bloom in the coastal waters, and model results manifest that discharge’s impact extends to the continental shelf 50 150 km away from the coastline. However, bottom nutrients are uplifted to contribute Chla enhancement in the upper and middle layer in the shelf. It is possible that nutrient transported from the open sea along continental slope with the bottom cold water to trigger Chla enhancement in the Taiwan Bank. This work suggests that strong tide and wave, regional dynamics and discharge should be considered to improve model skills in the future.